The use of the availability scale for interprofessional education in health in national publications - Rotta Bonfim, Mariana; Cunha de Souza, Bruna (Journal of Health Care, 2021)
Readiness for Interprofessional Learning Scale (RIPLS), stands out for its efficiency in the evaluation and direction of Interprofessional Education (IPE) initiatives. Objective: This study aimed to analyze the use of this scale in national surveys. Materials and Methods: The survey of articles was done at Pubmed, Capes Journals, SCIELO and LILACS using the descriptors "Interprofessional Education", "Higher Education", "Interprofessional Relations", "Teamwork", and "RIPLS". Results and Conclusions: 7 articles were identified that indicate a tendency to use RIPLS to evaluate EIP initiatives in undergraduate and permanent health education, with little research on availability throughout training. There are divergences in the version of the RIPLS applied and in the methods of analysis, facts that hinder the comparison of the studies. It is suggested to use the validated version of this tool, to present the results in graphs and / or tables, and to use statistical analyzes that guarantee the exploration and comparison of the data.
Keywords: Interprofessional Education; Higher Education; Interprofessional Relations